THE EFFECT OF ANXIETY LEVEL ON BURNOUT MODERATED BY WORK MOTIVATION OF NURSES IN THE INTEGRATED INFECTION SERVICE INSTALLATION AT DR. SAIFUL ANWAR HOSPITAL - Suyanto, Suyanto; Ahsan; Ratri, Devita Rahmani (Universitas Brawijaya, 2025)
The nursing profession plays a crucial role in healthcare, requiring both physical and psychological preparedness. Registered nurses (RNs) specializing in infectious disease care are particularly vulnerable to heightened anxiety due to the physical demands of their work, uncertainty in patient care, and the risk of infection. Prolonged exposure to these stressors can lead to burnout, ultimately compromising the quality of patient care. This study examines the effect of anxiety levels on burnout, with work motivation as a moderating variable, among nurses in the Integrated Infection Service Installation at Saiful Anwar Hospital. This study employs an observational analytic approach, utilizing a cross-sectional design. The data were collected from 72 nurses through a questionnaire and analyzed using the Moderated Regression Analysis (MRA) method. The results indicate a significant positive association between anxiety levels and burnout (path coefficient = 0.803, t-statistic = 4.965, p = 0.000), while work motivation exhibited a significant negative effect on burnout (path coefficient = -0.405, t-statistic = 3.160, p = 0.002). Additionally, work motivation moderated the relationship between anxiety and burnout, mitigating its impact (path coefficient = 0.179, t-statistic = 2.134, p = 0.033). These findings underscore the importance of fostering a work environment that enhances motivation through performance-based rewards, professional training, and collaborative relationships. Furthermore, integrating anxiety management programs, such as counseling and mindfulness training, is essential for reducing anxiety and preventing burnout among nurses working in infectious disease care settings.